2022
DOI: 10.3390/biomedicines10092151
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy in Head and Neck Cancer When, How, and Why?

Abstract: Head and neck cancer (HNC) is one of the most common cancers worldwide. Alcohol and tobacco consumption, besides viral infections, are the main risk factors associated with this cancer. When diagnosed in advanced stages, HNC patients present a higher probability of recurrence or metastasising. The complexity of therapeutic options and post-treatment surveillance is associated with poor prognosis and reduced overall survival (OS). This review aims to explore immunotherapy (immune checkpoint inhibitors (ICI), th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…However, chronic inflammation and immunological dysregulation may contribute to a slightly elevated risk as we will address in more detail. It is also important to highlight that, contrary to what we can observe in cell-mediated inflammatory diseases, the effectiveness of immunotherapy in treating HNC associated with humoral inflammatory diseases is still not well established [35]. Since these diseases involve complex immune system abnormalities, their interaction with immunotherapy agents may differ from that of cell-mediated diseases.…”
Section: Humoral Inflammatory Diseasesmentioning
confidence: 93%
“…However, chronic inflammation and immunological dysregulation may contribute to a slightly elevated risk as we will address in more detail. It is also important to highlight that, contrary to what we can observe in cell-mediated inflammatory diseases, the effectiveness of immunotherapy in treating HNC associated with humoral inflammatory diseases is still not well established [35]. Since these diseases involve complex immune system abnormalities, their interaction with immunotherapy agents may differ from that of cell-mediated diseases.…”
Section: Humoral Inflammatory Diseasesmentioning
confidence: 93%
“…Pembrolizumab, a PD-1 monoclonal antibody, made groundbreaking strides as the first immunotherapy for recurrent or metastatic head and neck squamous cell carcinoma. 44 The KEYNOTE studies, spanning Phases I-III, meticulously assessed its efficacy and safety. [45][46][47] Harrington et al 48 recently reported updated results from the Phase III KEYNOTE-048 study, showing that even after a 4-year follow-up, first-line pembrolizumab and pembrolizumab-chemotherapy still provided better survival outcomes compared to cetuximab-chemotherapy in recurrent/metastatic head and neck squamous cell carcinoma.…”
Section: Evolving Strategies Beyond the Scalpelmentioning
confidence: 99%
“…In such circumstances, immunotherapy is steadily earning recognition as a preferred choice for treatment. Pembrolizumab, a PD‐1 monoclonal antibody, made groundbreaking strides as the first immunotherapy for recurrent or metastatic head and neck squamous cell carcinoma 44 . The KEYNOTE studies, spanning Phases I–III, meticulously assessed its efficacy and safety 45–47 .…”
Section: Evolving Strategies Beyond the Scalpelmentioning
confidence: 99%
“…However, traditional treatments can cause significant side effects and may not be effective for all patients [ 3 , 4 ]. Recently, immunotherapy, including immune checkpoint inhibitors, has emerged as a promising treatment option for oral cancer [ 5 , 6 ]. Immune checkpoint inhibitors, such as those that target programmed cell death protein 1 (PD‐1), have shown encouraging results since they were approved in 2014 for the treatment of various solid tumors [ 7 ].…”
Section: Introductionmentioning
confidence: 99%